Urban Form Beyond Density: Shape Compactness Matters - Putri, Galuh Anisa; Gamal, Ahmad (CSID Journal of Infrastructure Development, 2025)
Urban compactness has traditionally been measured through density, with population per area used as a core indicator of urban form. However, this method creates a limited view of what compactness means. Research shows that a compact city is not always a high-density city, and that increasing density does not automatically result in compact development. Compactness also involves the shape and structure of urban footprints, which influence how land is used and how a city functions. This paper presents a conceptual distinction between density and shape compactness, arguing that both are necessary to understand urban form. A qualitative literature review was conducted to examine how cities with similar density levels can show major differences in spatial structure and performance. The findings suggest that density and shape are separate components of urban form. This paper proposes a broader measurement framework that includes both factors, which can improve spatial planning, urban design, and policy decisions.